2013
DOI: 10.1260/1708-5284.10.6.523
|View full text |Cite
|
Sign up to set email alerts
|

The effect of boron on the performance of automotive brake

Abstract: Friction material in an automotive brake system plays an important role for effective and safe brake performance. A single material has never been sufficient to solve performance related issues. Current research aimed to examine properties of Boron mixed brake pads by comparing them with the commercial brake pads. Friction coefficient of Boron mixed brake pads and commercial brake pads were significantly different and increased with the increase in surface roughness. The abrupt reduction of friction coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A Taylor Hobson Profilometer was utilized to estimate the amount of wear of the disk. Optical microscopy and SEM were utilized to examine the worn surface, and the X-ray spectrum was utilized to examine the wear debris [41]. Hybrid aluminum matrix composites reinforced with hexagonal boron nitride and graphene nanoparticles were prepared.…”
Section: Progress In Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Taylor Hobson Profilometer was utilized to estimate the amount of wear of the disk. Optical microscopy and SEM were utilized to examine the worn surface, and the X-ray spectrum was utilized to examine the wear debris [41]. Hybrid aluminum matrix composites reinforced with hexagonal boron nitride and graphene nanoparticles were prepared.…”
Section: Progress In Nanomaterialsmentioning
confidence: 99%
“…The wear particles whose diameter is less than 100 nanometers Fused mullite (i) Density reduced from 6.2 g/cc to 2.40-2.72 g/cc for three different samples (ii) The wear rate for the sample containing 3 wt% of mullite decreased from 1 g to 0.887 g [88] Nanosized SiO 2 particles (i) With the addition of 9% SiO 2 , there was an improvement of 18.11% in hardness & an increase of 5.4% in roughness [12] Phenolic resin (PF)/organized expanded vermiculite (OEVMT) (i) The brake pad based on PF exhibited a weight reduction ratio of 45.8%, whereas the brake pad based on PF/OEVMT exhibited a ratio of 77.1% (ii) For the PF/OEVMT brake pad, the coefficient of friction decreased by only 0.05, whereas for the PF based brake pad, the value decreased by 0.24 [39] Kaolin-TiO 2 (KATI) (i) The loss of pad thickness was 50% lower for the KATI-based brake pad which improved the durability [13] Boron (i) The coefficient of friction for the boron-based brake pad was 0.065 higher than its counterpart [41] Graphene/boron nitride with aluminum (i) Sample Al-1BN-0.15GNP exhibited an increase of 225% in ultimate compressive strength & an 87% increase in hardness values [42] Aluminum-silicon nitride (Al-Si 3 N 4 ) & aluminum-graphite-silicon nitride (Al-Gr-Si 3 N 4 ) (i) For the Al-Gr-Si 3 N 4 sample, the wear rate decreased by 25% when compared with the Al-Si 3 N 4 sample (ii) There was a reduction of 15% in the friction coefficient of the Al-Gr-Si 3 N 4 sample when compared with the Al-Si 3 N 4 sample [45] Al/SiC+B 4 C (iii) Wear resistance increased by 88.32% for the sample containing 1.5% SiC & 0.5% B 4 C as compared with a monolithic aluminum [14] 14 Journal of Nanomaterials method revealed that BP10 samples had the highest wear rate, whereas BP5/BG5 samples depicted the lowest values [38]. Superior thermal characteristics of the PF/OEVMTbased brake pad were confirmed by thermogravimetric analysis.…”
Section: Brake Pad Wear Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that friction materials containing boron have a coefficient of friction higher than ordinary, commercial brake pad -0,495. Additionally, it has been found that such materials have thermal stability up to 200 ∘ C [165,166].…”
Section: Abrasivesmentioning
confidence: 99%
“…19 Muzathik et al compared the brake pads with boron mixture with commercial pads and concluded that brake pads containing boron can be used against the fading problem. 20 Sugozu et al examined friction materials containing ulexite and concluded that ulexite material improved frictional stability and fade resistance. 21 Rajan et al investigated the effects of this binder on thermal stability and fading by using different ratios of Epoxy-Modified Phenolic (EMP) resin.…”
Section: Introductionmentioning
confidence: 99%